2019
DOI: 10.2147/cmar.s195123
|View full text |Cite
|
Sign up to set email alerts
|

<p>Novel nomograms individually predict the survival of patients with soft tissue sarcomas after surgery</p>

Abstract: Background: The aim of the study was to build and validate practical nomograms to better predict the overall survival (OS) and cancer-specific survival (CSS) of the patients with soft tissue sarcomas (STS) who underwent surgery. Methods: Patient data were extracted from the Surveillance, Epidemiology, and End Results (SEER) database. We identified 8804 patients who underwent surgery with STS between 2007 and 2015, and randomly divided them into the training (n=6164) and valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Furthermore, we demonstrated the ability of a five-gene dedifferentiation signature to stratify retroperitoneal DDLS into good and poor prognostic groups, and further showed that this prediction offers additional information beyond that provided by clinical information alone. This finding is complementary to work by other groups who developed nomograms utilising clinical data to predict recurrence and OS [ 22 , 23 , 24 ]. Potentially, a combination of both clinical and molecular information offers the best approach for the prognosis of patients as a clinical adjunct for more accurate patient counselling and improved identification of patients who may benefit from more aggressive treatment or adjuvant therapy for optimum disease control.…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, we demonstrated the ability of a five-gene dedifferentiation signature to stratify retroperitoneal DDLS into good and poor prognostic groups, and further showed that this prediction offers additional information beyond that provided by clinical information alone. This finding is complementary to work by other groups who developed nomograms utilising clinical data to predict recurrence and OS [ 22 , 23 , 24 ]. Potentially, a combination of both clinical and molecular information offers the best approach for the prognosis of patients as a clinical adjunct for more accurate patient counselling and improved identification of patients who may benefit from more aggressive treatment or adjuvant therapy for optimum disease control.…”
Section: Discussionsupporting
confidence: 62%
“…Nomogram is a graphical illustration of a statistical model for calculating the cumulative effect of several variables and can be used to predict individual survival outcomes. Nomograms have been established for a variety of cancers and have shown more accurate in predicting prognosis than traditional tools [ 14 19 ]. As far as we know, the present study is the first article to develop and validate the prognostic nomograms for both OS and CSS in patients with FS.…”
Section: Discussionmentioning
confidence: 99%
“…Undeniably, our study has several limitations that should be acknowledged. The first major limitation stemmed from the lack of information about the use of targeted drugs, dosage of radiotherapy, and details of chemotherapy regimens (20). Different regimens and responses are significantly associated with survival (21, 22).…”
Section: Discussionmentioning
confidence: 99%